Integrated English Skills Teaching through Movie Dubbing at Senior High School - Rosa, Wardatul Kamilah; Basya, Dihliza (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2024)
This research discusses the use of Islamic film dubbing as a teaching tool to improve students' English language skills, which include four skills, namely speaking, writing, reading, and listening by using video editing software as a tool to edit student videos for dubbing. This research uses classroom action research with eleventh-grade students. The subjects of this research were eleventh-grade students from one of the high schools in Jember. In this research, students in one class are divided into several groups, and later each group will make a voiceover video. In this research, researchers used interviews to obtain information from respondents after making dubbing videos, and tests to find out whether the application of dubbing videos improved students' abilities in speaking, reading, writing, and listening. Apart from that, observation activities were also carried out to see how these techniques were applied during the teaching and learning process, and documentation was also carried out to document and record important events that occurred in the field.